Renal Memo1 Differentially Regulates the Expression of Vitamin D-Dependent Distal Renal Tubular Calcium Transporters - Moor, Matthias B.; Haenzi, Barbara; Legrand, Finola; Koesters, Robert; Hynes, Nancy E.; Bonny, Olivier (Frontiers in Physiology, 2018)
Ablation of the Mediator of ErbB2-driven Cell Motility 1 (Memo1) in mice altered calcium homeostasis and renal calcium transporter abundance by an unknown mechanism. Here, we investigated the role of intrarenal Memo in renal calcium handling. We have generated a mouse model of inducible kidney-specific Memo1 deletion. The Memo-deficient mice showed normal serum concentration and urinary excretion of calcium and phosphate, but elevated serum FGF23 concentration. They displayed elevated gene expression and protein abundance of the distal renal calcium transporters NCX1, TRPV5, and calbindin D28k. When the mice were challenged by a vitamin D3 deficient diet, serum FGF23 concentration and TRPV5 membrane abundance were decreased, but NCX1 abundance remained increased. Collectively, renal distal calcium transport proteins (TRPV5 and Calbindin-D28k) in this model were altered by Memo- and vitamin-D dependent mechanisms, except for NCX1 which was vitamin D3-independent. These findings highlight the existence of distinct regulatory mechanisms affecting TRPV5 and NCX1 membrane expression in vivo.